THE USE OF RAILWAYS AS A MEANS OF TRANSPORTING AGRICULTURAL PRODUCTS ON THE SOLO-SEMARANG LINE 1864–1940: Penggunaan Kereta Api sebagai Alat Transportasi Hasil Perkebunan di Jalur Solo-Semarang Tahun 1864-1940 - Sulis Fathatun Nurleli; Djono Djono (Santhet: (Jurnal Sejarah, Pendidikan Dan Humaniora), 2026)
This study aims to examine the role of railways as a means of transporting agricultural products along the Solo–Semarang route during the period 1864–1940. The research method employed is the historical method, which consists of the stages of heuristics, source criticism, interpretation, and historiography. Research sources include colonial archives, NISM reports, photographic archives, as well as relevant books and articles. The results of the study indicate that the railway network played a significant role in the transportation of plantation products, particularly sugarcane, coffee, and tobacco. The integration of the rail network and the presence of lorries in plantation areas leading to processing factories demonstrate that the transportation of plantation products was already conducted systematically from the point of production. This means that before being transported to the main railway network, sugarcane was first transported via lorry routes connecting the plantations and processing factories. This indicates a connection between the railway network at the plantation level and the main railway network, thereby facilitating a smoother distribution process. Compared to traditional transport, railways were far more efficient, covering 110 km in about 3.5 hours, while traditional carts required up to 6 days. Railways also contributed to economic development, including the growth of markets, employment, and supporting businesses, and increased social mobility, although inequality persisted. In conclusion, railways functioned as the primary means of distribution for plantation products and played an important role in shaping economic and social change in the regions they served.